Pelatihan Aktivitas Fisik dengan tujuan Pencegahan Penyakit Persendian - Wahyana Mujari Wahid; Nur Fadly Alamsyah; Arimbi Arimbi; Haeril Haeril (Universitas PGRI Semarang, 2023)
ABSTRACTJoint disease is the occurrence of pain in the joints followed by a feeling of stiffness, redness and swelling which is not caused by a collision or accident (Ministry of Health, Republic of Indonesia, 2018). Basic health research (Riskesdas) shows that the prevalence of joint disease nationally reaches 7.30%. This data shows that joint disease is a disease that knows no age. The data shows that joint disease can attack a person from the age of 15 years. The purpose of this service is to provide education to the public about the risks faced when a person rarely does physical activityThe method of community service is carried out by socializing and training